Sinergi Peran Pemerintah Desa dan Masyarakat dalam Pengembangan Desa Wisata untuk Meningkatkan Kesejahteraan Masyarakat - Habibi, Muhammad Mujtaba (Universitas Negeri Malang, 2022)
This study aimed to describe the tourism village development program, the synergy of the village government and the community's role in the development of tourist villages, as well as improving community welfare through the development of tourist villages in Semen Village, Blitar Regency. This study used a qualitative approach with the type of descriptive research—sources of data in the form of primary data and secondary data. Data were collected by using observation, interview and documentation techniques. Data were analyzed using an interactive model from Miles and Huberman. The study results showed that the tourism village development program included physical development in the form of facilities and infrastructure and non-physical development in the form of community empowerment. The synergy of the village government influences the success of developing a tourist village through potential exploration and the community as coordinator, facilitator, implementer, and accelerator. Furthermore, developing tourist villages could improve community welfare, including income, clean settlements, education levels, and the fulfilment of health facilities.